Ecological sustainability of rice farms in Siak District, Riau, Indonesia - RACHMIWATI YUSUF; Usman M. Tang; Rahman Karnila; Indra Fuadi; Usman Pato (Society for Indonesian Biodiversity, 2020)
Abstract. Yusuf R, Tang UM, Karnila R, Fuadi I, Pato U. 2020. Ecological sustainability of rice farms in Siak District, Riau, Indonesia. Biodiversitas 21: 3797-3804. The research was conducted in Siak District, Riau Province, Indonesia from January to July 2018 in the four subdistricts of rice production centers. The purpose of this study was to identify the ecological conditions of rice farming, analyze the index and ecological sustainability status of lowland rice farming, and analyze the role of each ecological attribute that will have sensitivity to the management of wetland rice in the development of rice farming in the Siak District in the near future. There were 203 sample farmers selected by purposive sampling. Data collection was done by interview and field observation. The sustainability was analyzed using the Rap-Rice method with Multidimensional Scaling (MDS). The results of the Rap-Rice analysis of eight ecological attributes were analyzed; five attributes provided high sensitivity for Sungai Mandau, and three attributes provided high sensitivity for the subdistricts of Bunga Raya, Sabak Auh, and Sungai Apit. Attributes that provided high sensitivity for all subdistricts were attributes of land suitability with land use plans and land conversion rates. The average attributes of ownership of the farm area provided high sensitivity for only three subdistricts (Sabak Auh, Sungai Apit, Sungai Mandau). Based on ecological conditions, analysis of wetland rice farming in Siak District showed a sustainable category for Bunga Raya (56.10%), Sabak Auh (52.80%), and Sungai Mandau (54.90%) and less sustainability for Sungai Apit (48.80%).